ROLE OF RSS IN NATION-BUILDING THROUGH SOCIAL CONTRIBUTION - Chaple, Satish L; Diwan, Vivek M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Rashtriya Swayamsevak Sangh (RSS) is one of the largest voluntary organizations in the world, with a deep-rooted presence in India’s socio-political landscape. Founded in 1925 by Dr. K.B. Hedgewar, the RSS has played a significant role in shaping India's national identity and contributing to various social and developmental initiatives. The organization operates on the principle of selfless service (sewa) and has been actively engaged in various spheres such as education, rural development, disaster relief, healthcare, and social harmony. This article explores the role of RSS in nation-building through its social contributions, highlighting its impact on various aspects of Indian society.